Informal Entrepreneurship in the Age of Smart Society 5.0: Digital Adaptation, Platform Dependency, and Social Relationality among Street Vendors in Makassar (Tamaddun, 2025)
This study examines how informal entrepreneurs specifically how street vendors (Pedagang Kaki Lima/PKL) navigate digital transformation in the era of Smart Society 5.0. Unlike narratives of digital optimism that portray technology as universally empowering, our findings reveal an uneven adoption landscape marked by structural constraints, algorithmic dependency, and cultural frictions. Drawing on a qualitative design involving 30 PKL in Makassar, Indonesia, the present study conducted semi-structured interviews, participant observation, and policy analysis to assess how digital tools reshape economic practices and social relations. Results show that digital literacy functions as a form of social capital: younger vendors leverage social media, digital payments, and messaging-based sales to extend market reach, while older vendors experience technological anxiety, mistrust, and a heightened risk of exclusion. Rather than fully digitizing, most PKL adopt hybrid practices that integrate online orders with face-to-face transactions to maintain community ties and autonomy. Engagement with delivery platforms generates new dependencies through commission fees, rating systems, and algorithmic visibility, eroding interpersonal interactions that historically defined PKL commerce. These findings challenge the premise that Smart Society 5.0 inherently promotes digital inclusion and highlight the need for context-specific interventions that protect informal entrepreneurs from extractive platform logics.